Simex estimator for polynomial errors-in-variables model - Gontar, O.; Malenko, A. (Інститут математики НАН України, 2007)
For polynomial errors-in-variables model, the Simex estimator is constructed in such way that it is consistent, as the samples size grows and the size of auxiliary sample is ﬁxed. Then the estimator is modiﬁed in such a way that it shows good results for small samples without losing its asymptotic properties for large samples. Simulation studies corroborate the theoretical ﬁndings.